The The Role of Teachers in Implementation Social Care Education Character at Primary Schools - Mazda Leva Okta Safitri; Ali Mustadi; Heri Retnawati (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2021)
One of the most important characters and must be implemented by students is the character of social care. The teacher has a very important role in impntation of characters in schools. This study aims to describe the role of teachers in the implementation of social care character education in elementary schools. This type of research is a qualitative research with a phenomenological type. The researchers conducted interviews and gave questionnaires to 32 primary teachers in South Sumatra Province. The results of this study indicated that the teacher instills a social care character in the classroom by integrating social care character into learning materials and becoming good role models for students. Teachers also give punishment and rewards in order to encourage and discipline students. Teachers and schools have also carried out various activities to instill social care in students. It has also received support from many parents of students. To make social caring character education run optimally, several ways can do by the teacher is that the lesson plan that is made must be considered and by the elements of education, making study contracts and further increasing parental participation in students' social activities. Keywords: Social Care Education Character, Education Character, The Role of Teacher